PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN LKPD TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK V SD PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Febe Ririn Ariyani; Dayu Rika Perdana; Siti Nuraini; Frida Destini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study was the low critical thinking skills of fifth grade students at SD Negeri 4 Metro Utara in the subject of Pancasila Education due to teacher-centered learning practices. This study aimed to determine the effect of implementing the Jigsaw cooperative learning model assisted by Student Worksheets (LKPD) on students’ critical thinking skills and to examine the differences between the Jigsaw and Teams Games Tournament (TGT) cooperative learning models. This research employed a quantitative approach with a quasi experimental method using a nonequivalent control group design. The population consisted of all fifth-grade students at SD Negeri 4 Metro Utara, totaling 56 students. The sample was selected through purposive sampling, consisting of 18 students from class V B as the experimental group and 19 students from class V A as the control group. The experimental group was taught using the Jigsaw model assisted by LKPD, while the control group used the TGT model. Data were collected through a critical thinking skills test and observation of the implementation of the learning models in both classes. The results of the regression analysis indicated that the Jigsaw cooperative learning model assisted by LKPD had a significant effect on students’ critical thinking skills. The t-test results also showed a significant difference between the experimental and control groups. Therefore, the Jigsaw model assisted by LKPD is more effective than the TGT model in Pancasila Education learning.